Ministry of Finance Decree No. 249 of the Year 2023 Amending Certain Provisions of the Executive Regulations of the Value-added Tax Law = وزارة المالية قرار رقم 249 لسنة 2023 بتعديل بعض أحكام اللائحة التنفيذية لقانون الضريبة على القيمة المضافة - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic